PENDAMPINGAN DRAMATARI CALONARANG BALIAN BATUR DI DESA TUMBAKBAYUH, MENGWI, BADUNG SEBAGAI UPAYA PELESTARIAN SENI TRADISI BALI - I Ketut Muada; I Nyoman Astawan; I Nyoman Sadwika (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
Calonarang dance drama is a traditional Balinese performing art form that serves religious, magical, aesthetic, and social functions in the Balinese Hindu community. This dance drama serves not only as a form of entertainment but also as part of a cultural ritual passed down through generations. However, the development of modernization and changing interests of the younger generation have led to various challenges facing the survival of traditional arts groups, including those faced by the Calonarang Balian Batur dance drama group in Tumbak Bayuh Village, Mengwi District, Badung Regency. The main challenges include the limited regeneration of young dancers and musicians, limited artistic development, and suboptimal performance management and documentation. This community service activity aims to support the preservation of Calonarang Balian Batur dance drama by strengthening the artistic capacity and fostering the regeneration of group members. The methods used include participatory observation, interviews, dance technique training, character and expression strengthening workshops, and mentoring in rehearsals and performances. The results of this activity indicate an increase in the artistic abilities of members, increased participation of the younger generation, improved performance quality, and growing public awareness of the importance of preserving traditional Balinese arts. Thus, this mentoring program has a positive impact on the sustainability of arts groups and the strengthening of the local cultural identity of the Tumbakbayuh Village community.